Avaliação de argamassas cimentícias especiais com adição de fibras poliméricas eletrofiadas de PET e PVB - Milani, Ketlin Carolina (2020)
Mortar is widely used in the construction sector and it is mainly formed by Portland cement. In general, low tensile strength and deformation characteristics of cementitious based materials are related to its fragile structure and porosity properties. In this way, to develop more efficient composites, different materials have been incorporated into concrete and mortar mixes, such as polymeric materials. Not only the chemistry but also the additions morphology influences the behavior of cementitious materials, as an example, fibers improve the performance of ductility and elastic limits even when added at low amounts. Electrospinning is a more modern technique of producing continuous fibers with controlled morphology, allowing the formation of threads with diameters less than 1 µm. Thus, the development of new Portland cement composites through the combination with two different polymeric fibers obtained by electrospinning process are evaluated: poly (ethylene terephthalate) (PET) and poly (vinyl butyral) (PVB). The membranes formed by this process showed uniform morphology and an average diameter of 1,85 μm for PET fibers and 1,54 μm for PVB fibers, which were later stiffened in liquid nitrogen and crushed in a knife mill for separation. A heterogeneous composition of fiber dense agglomerates was observed in the PET sample through scanning electron microscopy (SEM), while the PVB sample showed small blocks of adhered fibers. Thus, a dispersion step in an ultrasonic processor for part of the specimens was added, but this process showed not efficient by degrading the surface of PVB fiber agglomerates. The fresh and hardened state of manufactured mortar with fiber addition of 0,125%, 0,250%, and 0,500% in relation to the cement mass were evaluated through the Brazilian Association of Technical Standards tests. In the fresh state was observed a slight increase in mass density, i.e. 11,23% for the 0,125% addition of PET without dispersion, a decrease in the content of incorporated air, i.e. 36,86% for the 0,500% addition of PET without dispersion, and a reduction of the consistency index with the worst workability, i.e. 13,81% for the 0,500% addition of PET with dispersion. However, to the same parameters, the mortar with PVB addition presented intermediate values. In the hardened state, the additions did not affect the mass density, but contributed to the reduction of capillarity. The 0,250% addition of PVB showed the best resistance to water absorption, with a reduction of 43,85%. Concerning mechanical strength, significant data obtained after statistical treatment with a non-parametric test were evaluated. The 0,125% PET addition without dispersion increased 12,26% of cylindrical specimens’ compressive strength. For the 0,250% PVB addition without dispersion the flexural tensile strength increased 10,95% and the compressive strength of prismatic specimens increased 27,49%.